2016
DOI: 10.15171/mejdd.2016.34
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Cancer in Golestan Province, Iran: A Review of Genetic Susceptibility and Environmental Risk Factors

Abstract: Esophageal squamous cell carcinoma (ESCC) is an aggressive tumor that is typically diagnosed only when the tumor has gained remarkable size, extended to peripheral tissues, and led to dysphagia. Five-year survival of advanced cancer is still very poor (19%), even with improved surgical techniques and adjuvant chemoradiation therapy. Therefore, early detection and prevention are the most important strategies to reduce the burden of ESCC. Our review will focus on the studies conducted in Golestan province, an ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 101 publications
1
38
1
Order By: Relevance
“…Extensive investigations suggested that PAHs exposure should be correlated with a variety of cancers, such as lung cancer, larynx cancer, breast cancer and esophageal cancer . However, the study on the association between PAHs exposure and cervical cancer is rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive investigations suggested that PAHs exposure should be correlated with a variety of cancers, such as lung cancer, larynx cancer, breast cancer and esophageal cancer . However, the study on the association between PAHs exposure and cervical cancer is rare.…”
Section: Introductionmentioning
confidence: 99%
“…17 Extensive investigations suggested that PAHs exposure should be correlated with a variety of cancers, such as lung cancer, 18 larynx cancer, 19 breast cancer 20 and esophageal cancer. 21,22 However, the study on the association between PAHs exposure and cervical cancer is rare. Cytological studies showed that B[a]P might enhance the persistent infection of HPV, resulting in an increase of HPV16 viral titers, 23 and thus leading to cancerization.…”
Section: Introductionmentioning
confidence: 99%
“…Iran is one of the countries with very high incidence of EC [8,26]. Some parts of Iran, which have common borders with Turkmenistan and Afghanistan countries, experience much higher incidence rates of this cancer.…”
Section: Forest Plot Of the Random-effect Meta-analysis For Asrs Ofmentioning
confidence: 99%
“…Based on studies, risk factors such as drinking hot tea, burned opium consumption, gastric Helicobacter pylori infection, family history of esophageal cancer, drinking contaminated water, inappropriate diet, low physical activity, and smoking are associated with EC incidence [19,55]. The genetic role is also a major contributor to the high incidence of EC in Golestan province, having one of the highest worldwide rates of this type of cancer incidence [56][57][58].…”
Section: Forest Plot Of the Random-effect Meta-analysis For Asrs Ofmentioning
confidence: 99%
“…After cancer of the stomach, it is the most common cancer in the Iranian population. Golestan province, one of the northern provinces of Iran, is considered as one of the high-risk areas for esophageal cancer, with an esophageal cancer incidence rate of 100 people per 100,000 people (Gholipour et al, 2016). Esophageal cancer has a complex and diverse etiology, and many genetic and nutritional factors are involved in its etiology.…”
Section: Introductionmentioning
confidence: 99%